2017
DOI: 10.1186/s12909-017-1040-y
|View full text |Cite
|
Sign up to set email alerts
|

The relationship between resident burnout and safety-related and acceptability-related quality of healthcare: a systematic literature review

Abstract: BackgroundThere has been increasing interest in examining the relationship between physician wellbeing and quality of patient care. However, few reviews have specifically focused on resident burnout and quality of patient care. The purpose of this systematic literature review of the current scientific literature is to address the question, “How does resident burnout affect the quality of healthcare related to the dimensions of acceptability and safety?”MethodsThis systematic literature review uses a multi-step… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
81
1
5

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 118 publications
(91 citation statements)
references
References 37 publications
4
81
1
5
Order By: Relevance
“…In addition to the negative clinical impacts on individuals, burnout negatively affects workplace organizations. In general, burnout among health care providers has been linked to increased absenteeism and attrition, as well as reduced quality of care and more frequent medical errors, potentially compromising patient safety …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition to the negative clinical impacts on individuals, burnout negatively affects workplace organizations. In general, burnout among health care providers has been linked to increased absenteeism and attrition, as well as reduced quality of care and more frequent medical errors, potentially compromising patient safety …”
Section: Introductionmentioning
confidence: 99%
“…In general, burnout among health care providers has been linked to increased absenteeism and attrition, as well as reduced quality of care and more frequent medical errors, potentially compromising patient safety. [6][7][8][9] According to the Job Demands-Resources Theory, burnout most often results from a prolonged, ongoing imbalance between work demands and job-related resources, whereby work demands significantly exceed job-related resources. 10 Job demands are defined as physical, social, or organizational aspects that require sustained physical or mental effort (eg, physical workload, time pressure, physical environment).…”
Section: Introductionmentioning
confidence: 99%
“…2 To confuse "no proof of effect" with "proof of no effect" is a common mistake well illustrated here. Furthermore, reported medical errors have been found to approximate observed medical errors with 84% congruence, 3 and burnout has consistently been found to relate to poor quality of care, [4][5][6][7] including other objective measures of quality. 8 The second misconception is the distinction between workplace wellness and well-being.…”
Section: In Replydburnout Is Not Associated With Increased Medical Ermentioning
confidence: 86%
“…Yet what is perhaps most problematic about wellness programs and initiatives is that the rhetoric often used to support them may exacerbate prejudice associated with mental disorders and disabilities, 6 erode physicians' employment rights, 6 and result in other unintended adverse effects. Dozens of recent articles regarding the concerns of disability rights advocates about the discriminatory effects of workplace wellness programs on employees with disabilities appear in law and policy journals.…”
mentioning
confidence: 99%
“…Ultimately, these reactions can lead to health professionals being more likely to leave the workforce following a critical incident (de Boer et al, 2011;Seys et al, 2013). A literature review by Dewa, Loong, Bonato, Trojanowski, and Rea (2017) found a correlation between errors and burnout, subsequently further impacting performance and patient safety. Supportive environments have the potential to mitigate some of the impact on practitioner well-being and the patient care health professionals provide (Bynum & Goodie, 2014;Pezaro, Clyne, Turner, Fulton, & Gerada, 2016;Pinto, Faiz, & Vincent, 2012;Scott et al, 2010;Wu, Singh-Carlson, Odell, Reynolds, & Yuhua, 2016).…”
Section: Critical Incidents and The Impact On Health Professionalsmentioning
confidence: 99%